Homing in on endogenous badnaviral elements: Development of multiplex PCR-DGGE for detection and rapid identification of badnavirus sequences in yam germplasm - Silva, G.; Bömer, M.; Turaki, A.A.; Nkere, C.; Kumar, P. Lava; Seal, S. (Frontiers Media, 2022)
Viruses of the genus Badnavirus (family Caulimoviridae) are double-stranded DNA-reverse transcribing (dsDNA-RT) plant viruses and have emerged as serious pathogens of tropical and temperate crops globally. Endogenous badnaviral sequences are found integrated in the genomes of several economically important plant species. Infection due to activation of replication-competent integrated copies of the genera Badnavirus, Petuvirus and Cavemovirus has been described. Such endogenous badnaviral elements pose challenges to the development of nucleic acid-based diagnostic methods for episomal virus infections and decisions on health certification for international movement of germplasm and seed. One major food security crop affected is yam (Dioscorea spp.). A diverse range of Dioscorea bacilliform viruses (DBVs), and endogenous DBV (eDBV) sequences have been found to be widespread in yams cultivated in West Africa and other parts of the world. This study outlines the development of multiplex PCR-dependent denaturing gradient gel electrophoresis (PCR-DGGE) to assist in the detection and analysis of eDBVs, through the example of analysing yam germplasm from Nigeria and Ghana. Primers targeting the three most prevalent DBV monophyletic species groups in West Africa were designed to improve DGGE resolution of complex eDBV sequence fingerprints. Multiplex PCR-DGGE with the addition of a tailor-made DGGE sequence marker enables rapid comparison of endogenous badnaviral sequence diversity across germplasm, as illustrated in this study for eDBV diversity in yam.